The new CIO leader : setting the agenda and delivering results - Broadbent, Marianne; Kitzis, Ellen (Boston : Harvard Business School Press, 2005)
"Drawing from exclusive research conducted by Gartner, Inc., with thousands of companies and CIOs, Marianne Broadbent and Ellen Kitzis reveal exactly what CIOs must do now to solidify their credibility with the executive team and bridge the chasm that currently separates business and IT strategy. The New CIO Leader outlines the agenda CIOs need to integrate business and IT assets in a way that moves corporate strategy forward - whether a firm is floundering, successfully competing, or leading its industry. Mandatory reading for CIOs in every firm, The New CIO Leader spells out how information systems can deliver results that matter - and how CIOs can become the enterprise leaders they should be."--Jacket.
The new CIO leader -- Understand the fundamentals of your environment -- Create your vision -- Shape and inform expectations for an IT-enabled enterprise -- Create clear and appropriate IT governance -- Weave business and IT strategy together -- Build a new IS organization -- Build a high performing team -- Manage enterprise and IT risks -- Communicate your performance.
Includes bibliographical references (pages 319-325).
Print version record.
Master record variable field(s) change: 082
Keywords: Chief information officers; Information technology -- Management; Information resources management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Chief information officers; Information resources management; Information technology -- Management; Bedrijfsbeleid; Informatiemanagement; Informationstechnik; Management; elektronické knihy; electronic books